Striking an Emotional Chord: Effects of Emotional Appeals and Chatbot Anthropomorphism on Persuasive Science Communication - Wang, Jinping; Peng, Lulu (Science communication, 2023)
Chatbots have been used to achieve persuasive goals in various communication contexts. This research investigates how chatbot anthropomorphism intersects with emotional appeals to influence persuasive outcomes in science communication by conducting two experiments in the contexts of skin cancer prevention and biodiversity conservation. The findings showed a matching effect between emotional appeals and anthropomorphic cues: For a chatbot with more anthropomorphic cues, fear appeals were more persuasive than hope appeals; in contrast, for a less anthropomorphic chatbot, hope appeals were more effective. A key psychological mechanism underlying the relationships was personal risk perceptions but only for fear appeals.